Lived Experience of Infertility among Community Dwelling Infertile Women - Bista, Bishnu (Journal of Nobel Medical College, 2015)
Objective: The aim of this study was to investigate the lived experiences of infertility among infertile women in Jhapa. Methods: A descriptive phenomenological research design was utilized that is supported by philosophy of Edmund Husserl. Seven informants, who were having infertility problems selected for in-depth interviews, utilized purposive sampling technique. Information gathered from two Focused Group Discussions that included 20 participants and five key informants’ interviews were conducted to triangulate data source which obtained from study informants. Data were recorded and transcribed verbatim later. Transcribes were deducted to extract actual meanings through coding, categorizing and organized into theme clusters. Results: Informants experienced any one or all form of abuse like physical, emotional, psychological, societal or marital. Severity of torture depend on who had fertility related problems and infertile woman’s position in husband’s house. They believed their infertility problems are deeply rooted with social and cultural stigma of the society. Women, who were young and less than 15years of marriage duration, had more hope to become mother. Due to economic hardship and limited family support, they could not access to utilize Assisted Reproductive technologies. Conclusion: though the up lift of education, media and local non-governmental organizations support and changing concepts of society, infertile women experienced risk of being isolated in social activities, threaten to divorce and remarry by husband. Accepting the realities, supporting and understanding of each other’s’ limitations are core factor of husband wife relationship. Journal of Nobel College of Medicine Vol.4(1) 2015: 46-56